Microbial communities of the upper respiratory tract in mild and severe COVID-19 patients: a possible link with the disease course - Galeeva, Julia S.; Starikova, Elizaveta V.; Fedorov, Dmitry E.; Manolov, Alexander I.; Pavlenko, Alexander V.; Konanov, Dmitry N.; Krivonos, Danil V.; Babenko, Vladislav V.; Klimina, Ksenia M.; Veselovsky, Vladimir A.; Morozov, Maxim D.; Gafurov, Ilshat R.; et al. (Frontiers in Microbiomes, 2023)
The microbiota of the respiratory tract remains a relatively poorly studied subject. At the same time, it is involved in modulating the immune response to infectious agents in the host organism, just like the intestinal microbiota. A relationship between the composition of the respiratory microbiota and the likelihood of development and the severity of COVID-19 may be assumed. In this study, we applied 16S rRNA metagenomic sequencing to analyze the oropharyngeal swabs from 120 COVID-19 patients collected during the first and the second waves of the COVID-19 epidemic in Russia. Differential abundance analysis with respect to comorbidities suggested association of Neisseria oralis, Neisseria mucosa, unidentified Veillonella spp., Lautropia mirabilis species with more severe lung damage, and Streptococcus salivarius, Capnocytophaga sputigena and Haemophilus parahaemolyticus with a milder course of the disease. We hypothesize that the latter bacteria (or some of them) might be beneficial for the respiratory tract and might be able to alleviate the course of the COVID-19 disease